2005
DOI: 10.1111/j.1745-4522.2005.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Lipid Profile of New Zealand Marine Species Over Four Seasons

Abstract: New Zealand Greenshell mussels and hoki are caught throughout the year and oil is extracted from the processing discards. However, there is little information on the variability in the lipid profile during the annual cycle. The livers of male and female hoki (Macruronus novaezelandiae), Greenshell mussels (Perna canaliculus), blue mussels (Mytilus edulis aoteanus) and rock oysters (Saccostrea cucullata) were therefore collected four times during a 12-month period, and their lipid and lipid-soluble components w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
11
28
1
Order By: Relevance
“…We collected the spring sample in March, which was before spawning, and this had higher lipid content than the other three seasons. This result is agreement with studies in NZGLM [14] and in Chinese mussel Mytilus edulis (Linne) [2], and in other marine invertebrates such as Silurus asotus [16], Ostrea edulis (L) [17] and Haliotis rubra [18].…”
Section: Lipidssupporting
confidence: 92%
See 1 more Smart Citation
“…We collected the spring sample in March, which was before spawning, and this had higher lipid content than the other three seasons. This result is agreement with studies in NZGLM [14] and in Chinese mussel Mytilus edulis (Linne) [2], and in other marine invertebrates such as Silurus asotus [16], Ostrea edulis (L) [17] and Haliotis rubra [18].…”
Section: Lipidssupporting
confidence: 92%
“…b-sitosterol, a predominant phytosterol, was only present in minor amounts (2-5% of total sterol) in P. viridis. Plankton is the predominant diet of mussels, which contains various sterols, and they can be incorporated into mussel tissues, and some sterols such as cholesterol can be synthesized from plankton cholesterol precursors [16].…”
Section: Lipidsmentioning
confidence: 99%
“…However, lipid content of U. terminalis was found to be higher than in P. littoralis. For several mussel species, similar total lipid contents were reported by Şengör et al (1997) and Mclean and Bulling (2005). Statistical analysis results showed that no significant differences were observed between U. terminalis and P. littoralis in terms of protein, ash and moisture.…”
Section: Resultssupporting
confidence: 69%
“…The oil from New Zealand Greenshell mussel may have pharmaceutically valuable compounds (Jeffs et al 1999, McLean & Bulling 2005, Wolyniak et al 2005; Broadbent and Kosuge, stabilized mussel extract, NZ patent 211928). The major lipid classes of marine lipids are triacylglycerol, phospholipids, and sterols.…”
Section: Introductionmentioning
confidence: 98%
“…The New Zealand Greenshell mussel, Perna canaliculus, is widely farmed in New Zealand and is the most important commercial shellfish in both domestic and export markets (McLean & Bulling 2005). About 87% of the mussel harvest undergoes the heat shucking process (Gupta 2012).…”
Section: Introductionmentioning
confidence: 99%